Mejora y Calibración Mediante la Inspección Del Modelo de Priorización de Obras de Infraestructuras de Drenaje (Mpoid) - Araya-Porras, Enoc Adolfo (Instituto Tecnológico de Costa Rica, 2013)
Investment planning in the area of road is one of the lowest points in the public administration. The main problem in the maintenance is ignorance of the existing structures, conditions of this structures and the relationship between the environment and the road. This model is about network-level management that aims to be a tool for defining maintenance policies in drainage works, also is important the fact that the model is part of the unbundling of vial structures in its main elements, pavements, slope and restraint systems and drainage infrastructure, this for the purpose of efficient management of the budget, because it defines the elements that really are needed to improve the conditions of the road network. In this model involves seven subcriteria, which are grouped into three main criteria, socioeconomic, environmental and infrastructure. The weighting is performed using the multicriteria evaluation, which in order to obtain a complete evaluation is simplified user in a simple sorting that for the decision maker is becomes a fairly simple task. The sources that supply the model come from different institutions, such as Instituto Nacional de Estadistica y Censos, Ministerio Nacional de Planificación y Políticas Económicas, Consejo Nacional de Vialidad, Municipalities, Comisión Nacional de Emergencias, PRUGAM and research projects related to civil engineering graduate and construction.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2013.
Keywords: Planificación; Inversiones públicas; Construcción de carreteras; Costa Rica